Posted by Shawn on Sunday, November 30, 2008 at 6:22pm.
Find (fog)(x)and (gof)(x)if f(x)=x-x^2 and g(x)= 2x+3.
Okay so I did the following:
For f(of)g(x), take (2x+3) - (2x+3)^2
(insert g(x) where the "x" is in f(x) )
For g(of)f(x), take 2[x-x^2] +3
The first answer that I get for (2x+3) - (2x+3)^2 is -4x^2-12x-9
The second answer that I get for
2[x-x^2] +3 is 2x-2x^2+3
are these the answers to the problem?
Answer This Question
More Related Questions
- college algebra - 1. answer the following for the given quadratic function f(x)=...
- Algebra - If f(x)= ln x, g(x) = e^3x, and h(x) = x^7, find the following... a) (...
- Algebra help - Find (fog)(x)and (gof)(x)if f(x)=x-x^2 and g(x)= 2x+3.
- Algebra 2 - If f(x) = x-3 g(x) = 2x+5 find fog and gof
- Composite Functions - f(x)=(7x+28)/(x-3) and g(x)=(3x+28)/(x-7) Find: (fog)(x) (...
- math - 1. Let f : Z to Z and g : Z to Z be functions de fined by f (x) = 3x + 1 ...
- Algebra - When Let f (x) = x^2 – 3x + 8 and g(x) = x – 5 Find Find the composite...
- Maths - Let f(x)= 2x+1 and g(x) = 3x^2-4 find: a) f^-1 b) gof (-2) c) fog (x)
- Pre Calculas - Im really struggling and need help with this 1. One of the tables...
- math - Find a. fog b. gof c. fof d. gog f(x)=4-x g(x)=3x-5